Hubungan antara Tayangan Drama Serial Korea X dengan Minat Mahasiswa menjadi Reporter - Azka Muzakiah; Wulan Trigartanti (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. The world has been faced with changes in the digital era, especially in the field of information communication which makes it easier for humans to access various information. whether in the form of news, advertisements, radio broadcasts, film shows to dramas. Drama shows, especially dramas from Korea, are very popular among the public, seen from the birth of the term Korean wave. The various themes raised made the storyline more diverse, one of which was the Times drama series which picked up a reporter's story. So the researchers are interested in researching the Times drama shows with the audience's interest in becoming reporters. The purpose of this study was to determine the relationship between the Times drama program and the audience's interest in becoming a reporter. The theory used is mass communication process theory, media exposure theory, and social learning theory. The method used is a quantitative correlational approach with data collection techniques through questionnaires, observation, and literature. The questionnaire was distributed to 79 respondents at the Faculty of Communication Unisba 2017 and analyzed by statistical tests with the SPSS application. The results of this study obtained a correlation coefficient with the number 0,772 it can be interpreted that there is a strong relationship between drama shows and the variable of interest in being a reporter Abstrak. Dunia telah dihadapkan oleh perubahan era yaitu digital, khususnya pada bidang komunikasi informasi yang menyebabkan manusia menjadi lebih mudah untuk mengakses berbagai informasi. baik dalam bentuk berita, iklan, siaran radio, tayangan film hingga drama. Tayangan drama khususnya drama dari negara Korea sangatlah populer dikalangan masyarakat, dilihat dari lahirnya sebutan yaitu gelombang Korea. Berbagai tema yang diangkat membuat alur cerita semakin beragam, salah satunya drama serial Times yang mengangkat cerita cerita reporter. Maka peneliti tertarik meneliti mengenai tayangan drama Times dengan minat penonton menjadi reporter. Tujuan penelitian ini untuk mengetahui hubungan antara tayangan drama Times dengan minat penonton menjadi reporter. Teori yang digunakan yaitu teori proses komunikasi massa, teori terpaan media, dan teori pembelajaran sosial. Metode yang digunakan adalah kuantitatif pendekatan korelasional dengan teknik pengumpulan data melalui kuesioner, observasi, dan studi pustaka Kuesioner disebar kepada 79 responden di Fikom Unisba angkatan 2017 serta dianalisis oleh uji statistika dengan aplikasi SPSS. Hasil penelitian ini diperoleh koefisien korelasi dengan angka 0,772 yaitu dapat diartikan terdapat hubungan yang kuat antara tayangan drama dengan variabel minat menjadi reporter